2021
DOI: 10.1177/21925682211031514
|View full text |Cite
|
Sign up to set email alerts
|

Aggravation of Ossified Ligamentum Flavum Lesion Is Associated With the Degree of Obesity

Abstract: Study Design: Retrospective cross-sectional study. Objectives: There is insufficient data on the clinical features of ossification of the ligamentum flavum (OLF) of the thoracic spine and the risk of progression of ossified lesions. The link between obesity and ossification of the posterior longitudinal ligament (OPLL), which frequently coexists with OLF, has been demonstrated. However, the link between obesity and OLF has not been recognized. We aimed to determine the prevalence of obesity in thoracic OLF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 21 publications
(43 reference statements)
1
28
0
Order By: Relevance
“…Obesity is more common in symptomatic OLF and T-OPLL, with a strong ossi cation tendency of the entire spinal ligament. [12,13] In addition, OLF and C-OPLL are more likely to occur in men, [6,29] whereas T-OPLL is more likely to occur in women. [5] Our results con rm the previous ndings; however, we would like to emphasize that our results are not necessarily synonymous with the risk of worsening ossi ed lesions, because the present study was based on a risk analysis of an increased prevalence of OLF and OPLL, and included many asymptomatic subjects with relatively small ossi ed lesions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Obesity is more common in symptomatic OLF and T-OPLL, with a strong ossi cation tendency of the entire spinal ligament. [12,13] In addition, OLF and C-OPLL are more likely to occur in men, [6,29] whereas T-OPLL is more likely to occur in women. [5] Our results con rm the previous ndings; however, we would like to emphasize that our results are not necessarily synonymous with the risk of worsening ossi ed lesions, because the present study was based on a risk analysis of an increased prevalence of OLF and OPLL, and included many asymptomatic subjects with relatively small ossi ed lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Recent epidemiological studies have reported that obesity is a common aggravating factor in patients with diffuse types of OPLL and OLF, in which the entire spinal ligament tends to ossify. [10][11][12][13][14][15] This suggests that lifestyle-related diseases and visceral obesity may be involved in the development and progression of these conditions. [11][12][13] Dyslipidemia is caused by malnutrition, obesity, sarcopenic obesity, and genetic predisposition and is closely related to metabolic disturbances.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, concrete evidence has identified obesity as an independent causal factor for the development of OLF in non-elderly adults ( 8 ). A recent cross-sectional study also demonstrated the aggravation of OLF associated with the degree of obesity ( 9 ). These findings revealed obesity might not only act as a starter but also a facilitator of OLF.…”
Section: Introductionmentioning
confidence: 92%